Characterisation of a subaqueously-deposited silt iron ore tailings. Issue 4 (9th October 2018) - Reid, David; Fanni, Riccardo; Koh, Kai; Orea, Ivan
Abstract : A geotechnical investigation was carried out to characterise a subaqueously-deposited, primarily silt, iron ore tailings. Piezocone penetration tests (CPTu) were carried out followed by piston tube sampling at a selected target depth. Piston samples provided measures of in situ density (by means of gravimetric water content), and supplied material for reconstituted and intact laboratory testing. Reconstituted samples prepared using moist tamping (MT) for determination of the critical state locus (CSL), along with intact specimens, were both tested. The potential existence of layering within the recovered specimens was also assessed, indicating near-homogenous samples. The laboratory testing of intact specimens suggested that they appeared to tend towards the same CSL as that obtained from reconstituted loose MT specimens. This tentative result differs from some previous comparisons – with the agreement seen in this case being suggested to primarily result from a lack of layering. In situ state as inferred from both CPTu data and comparison of tube densities to the CSL suggested a loose state.